2020
DOI: 10.1002/stab.202000021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flange dimensions and geometrical imperfections on stress concentrations at welded flange necks

Abstract: Ring flange connections for tubular towers, like those for wind turbines or chimneys, are subjected to significant fatigue loading. Next to the bolts, the weld connecting the flange to the tower shell also needs to be checked against fatigue failure. The flange causes local bending moments in the shell, which increase the meridional stress, i. e. stress concentrations occur. In this paper, the influence of geometrical imperfections on such stress concentrations is quantified and the influence of flange geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As the stress state from closing the parallel flange gap results in meridional compressive stress at the end of the gap (see Fig. 7 in [5]), the gap was centred at θ b = π/2 + π/6 so as to align its associated peak meridional compressive stress most detrimentally with the direction of bending as illustrated by Fig. 1.…”
Section: Base Casementioning
confidence: 99%
See 3 more Smart Citations
“…As the stress state from closing the parallel flange gap results in meridional compressive stress at the end of the gap (see Fig. 7 in [5]), the gap was centred at θ b = π/2 + π/6 so as to align its associated peak meridional compressive stress most detrimentally with the direction of bending as illustrated by Fig. 1.…”
Section: Base Casementioning
confidence: 99%
“…The parallel flange gap [3][4][5] is a gap relating to the interface flatness tolerance of prEN 1993-1-6 [8] and occurs 'in between flanges before bolts are tightened' [4]. The sinusoidal shape of the gap has been defined by Equation ( 5) based on Equation 4 of Holst and Rotter [10] as…”
Section: Parallel Flange Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical approach was compared with a 3D finite element model showing good agreement. In a later paper, Seidel et al [17] investigated the impact of flange dimensions and imperfections in the flange geometry on these SCFs. It was found that connections with large shell thicknesses are increasingly likely to be critical, additionally, it was noted that geometric imperfections have negligible influence on the SCFs.…”
Section: Introductionmentioning
confidence: 99%